2014
DOI: 10.1007/s00246-014-0996-1
|View full text |Cite
|
Sign up to set email alerts
|

Moving Towards Universal Prenatal Detection of Critical Congenital Heart Disease in Southern Nevada: A Community-Wide Program

Abstract: This study compares the current, prenatal detection rate for critical congenital heart disease in Southern Nevada with the previously reported rate, after developing and expanding a comprehensive, community-wide fetal cardiology program. For the current-period analysis, we inquired our database and electronic health records for patients born in Clark County, Nevada, with critical congenital heart disease between May 2012 and April 2014, and we compared the results with the previous period between May 2003 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 33 publications
1
56
0
Order By: Relevance
“…During this period, our prenatal detection rate for a RAA was 85%. We previously reported the results of how our regionalized fetal cardiology program, which over time has improved the detection of significant congenital heart disease . Briefly, our approach consists of ongoing community‐wide educational programs for general obstetric and specialized perinatal sonographers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this period, our prenatal detection rate for a RAA was 85%. We previously reported the results of how our regionalized fetal cardiology program, which over time has improved the detection of significant congenital heart disease . Briefly, our approach consists of ongoing community‐wide educational programs for general obstetric and specialized perinatal sonographers.…”
Section: Discussionmentioning
confidence: 99%
“…Right aortic arch, VR, presence and position or absence of the ductus arteriosus were all identified by either fetal echocardiography, neonatal echocardiography if the ductus arteriosus were patent, computed tomography, magnetic resonance imaging, or cardiac catheterization and angiography. We undertook fetal cardiovascular evaluations, as we previously reported . We defined a prenatal detection rate as the number of patients detected prenatally divided by the total number of patients identified that were born during the evaluation period.…”
Section: Methodsmentioning
confidence: 99%
“…Our data suggest that training programs in detection of CHD by screening obstetric ultrasound should be targeted to these impoverished, rural communities for the greatest impact. Supervision of imaging and specialized training on normal findings for more complex views has been demonstrated to be effective by Evans et al and could be a focus for continuing education …”
Section: Discussionmentioning
confidence: 99%
“…Despite previous reports, we do not consider a left aortic arch with an aberrant right subclavian artery a vascular ring or a “partial” vascular ring, and no such patients were included in this analysis. We undertook fetal cardiovascular evaluations as previously reported . We defined a prenatal detection rate as the number of patients detected prenatally divided by the total number of patients identified that were born during the study period.…”
Section: Methodsmentioning
confidence: 99%